Analysis of the Effectiveness of Project-Based Learning in Improving High School Students Motivation in Speaking - Silviana Simatupang; Benni Ichsanda Rahman Hz (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study is aimed to investigate the impact of Project-based learning (PjBL) on enhancing motivation among high school students in English speaking proficiency. Utilizing a qualitative case study approach, data was gathered through questionnaires and interviews. The sample of this study is 16 students in the 11th grade at a Public Senior High School in Medan, aged between 16-17 years old, selected through purposive sampling. The participant engaged in PjBL activities in their English speaking class, where their motivation levels were assessed before and after the implementation of PjBL. The finding revealed a significant increase studentsâ€™ motivation and confidence in speaking English following their participation in PjBL activities.This study contributes to the understanding of how PjBL can positively impact studentsâ€™ motivation in language learning, emphasizing the need for further research in diverse educational settings.Â